Metagenomic and Metabolomic Profiling Reveals the Differences of Flavor Quality between Hongqu Rice Wines Fermented with Gutian Qu and Wuyi Qu - Zihua Liang; Shiyun Chen; Hao Wang; Qi Wu; Weiling Guo; Li Ni; Xucong Lv (Foods)
Jiuqu (starter) makes an important contribution to the formation of the flavor characteristics of Hongqu rice wine (HQW). Gutian Qu (GTQ) and Wuyi Qu (WYQ) are two kinds of Jiuqu commonly used in HQW brewing, but the comparison of the two kinds of HQW is still insufficient at present. The objective of this study was to compare the dynamic changes of amino acids (AAs), higher alcohols (HAs), bioamines (BAs), volatile flavor compounds (VFCs), and microbial communities in HQW fermentation, with GTQ and WYQ as starter. This study used an automatic amino acid analyzer, GC, HPLC, and GC-MS to detect AAs, HAs, Bas, and VFCs during fermentation; metagenomic sequencing technology was used to elucidate the microbial community and its functional characteristics. The results showed that the contents of AAs and HAs in HQW brewed with WYQ (WYW) were significantly higher than those in HQW brewed with GTQ (GTW). On the contrary, the majority of BAs in GTW were significantly higher than those in WYW. The composition of VFCs in WYW and GTW were obviously different, as most of the VFCs were notably enriched in WYW, while ethyl caproate, isoamyl acetate, ethyl heptanoate, ethyl nonanoate, 1-decanol, citronellol, phenethyl acetate, and hexanoic acid were more abundant in GTW. Burkholderia gladioli, Pantoea dispersa, Weissella cibaria, Monascus purpureus, and Saccharomyces cerevisiae were the predominant microbial populations in GTW brewing at the species level, while Sphingomonas sp., Kosakonia cowanii, Enterobacter asburiae, Leuconostoc lactis, Aspergillus niger, and Saccharomyces cerevisiae were the dominant microbial species in WYW brewing. The abundance of functional genes involved in BAs biosynthesis were much higher in GTW brewing, while the abundance of functional genes related to the metabolism of characteristic VFCs were much higher in WYW brewing. Collectively, these findings provided evidence for elucidating the effects of Jiuqu and microbial communities on HQW flavor quality, and laid a solid foundation for the improvement of HQW flavor quality.